Brasil: idéia de diversidade e representações sociais - Bôas, Lúcia Pintor Santiso Villas (2008)
This paper is part of a wider project, Imaginary and Social Representations of University Students about Brazil and Brazilian schools that, in turn, created the Latin- American Imaginaries International Program, carried out at Laboratoire Europeen de Psychologie Sociale of Maison des Sciences de l'Homme (France). This study included the participation of a group of public and private university students from five Brazilian regions with the purpose of compiling the history of social representations throughout the country associated with diversity by analyzing convergent aspects between their current representational content and the historiographic production of the 19th century a period that saw organizing the national State and automating a collection of speeches on the significance of Brazil while making it essential to analyze the generative processes of such representations. To do so, theoretical-methodological procedures were established based on computerized text analysis (Max Reinert), as well as on aspects of historical effects (Hans-Georg Gadamer) and of the history of concepts (Reinhart Koselleck), with the purpose of considering conceptual delimitations of contemporaneity and of the 19th century in relation to diversity. The findings reveal the presence of a network of meanings synthesized within the following theme contexts: coexistence of contrary; cultural variety; space of experience; horizon of expectation and guiding fiction. The analysis of this network makes the appropriation of set meanings attributed to the 19th century visible; however receiving another semantic extension, today still helps organize the social representations about Brazil in addition to indicating the permanence of a repetitive structure, whose stability is kept even before the change in historical contexts